Relationship between parenting styles and depression in adolescents (Dhaka University Journal of Biological Sciences, 2019)
This study aimed at examining the relationship between parenting styles and depression in adolescents. Convenient sampling was used to collect 100 adolescents (Mean age = 15.25 years, Sd = 0.90) from two colleges of Dhaka city, Bangladesh. Parental Attitude Questionnaire (PAQ) was used to measure parenting styles and two other self-report measures, Hospital Anxiety and Depression Scale (HADS) and Short Mood and Feelings Questionnaire (SMFQ) were used to assess depression in adolescents. From multiple regression analysis significant relationship was found between parenting style and adolescents’ depression measured by one self-rating scale. The overall regression model for investigating the relationship between parenting style and depression in adolescent was significant with HADS, (F = 3.77, p = 0.007) but not significant with SMFQ scores (F = 0.880, p = 0.454). For the dependent variable of depression measured by HADS, the strongest predictors were authoritative parenting style (β = –0.28, p = 0.03) and monthly income of the family which is also significant (β = 0.25, p = 0.01). Implications of the findings for child rearing and research are discussed.Dhaka Univ. J. Biol. Sci. 28(1): 49-59, 2019 (January)